The Acute Effects of Time-Varying Caloric Vestibular Stimulation as Assessed With fMRI - Black, Robert D.; Bell, Ryan P.; Riska, Kristal M.; Spankovich, Christopher; Peters, Richard W.; Lascola, Christopher D.; Whitlow, Christopher T. (Frontiers in Systems Neuroscience, 2021)
We describe preliminary results from the application of time-varying caloric vestibular stimulation (tvCVS) to volunteers during a continuous BOLD fMRI acquisition, recording baseline, during-tvCVS and post-tvCVS epochs. The modifications necessary to enable the use of this novel device in a 3-Tesla magnetic field are discussed. Independent component analysis (ICA) was used as a model-free method to highlight spatially and temporally coherent brain networks. The ICA results are consistent with tvCVS induction being mediated principally by thermoconvection in the vestibular labyrinth and not by direct thermal effects. The activation of hub networks identified by ICA is consistent with the concept of sensory neuromodulation, which posits that a modulatory signal introduced to a sensory organ is able to traverse the regions innervated (directly and indirectly) by that organ, while being transformed so as to be “matched” to regional neuronal dynamics. The data suggest that regional neurovascular coupling and a systemic cerebral blood flow component account for the BOLD contrast observed. The ability to modulate cerebral hemodynamics is of significant interest. The implications of these initial findings for the use of tvCVS therapeutically are discussed.